Comparison of local anaesthesia versus spinal anaesthesia for peri anal disorders - Sukha Singh; Sudhir Khichy; Bhupinder Singh; Joginder Pal Attri (International Journal of Medical Research and Review, 2017)
Background: Peri anal disorders are associated with high morbidity and can be managed surgically both under spinal as well as local anaesthesia.Objectives: The study evaluates the results of anal surgery when performed under local anaesthesia as compared to spinal anaesthesia with respect to parameters like post operative pain, nausea, vomiting, analgesia requirement, voiding problem and bleeding.Material and Methods: The study included 50 patients divided in two groups (A and B) of 25 each. The patients of group A and group B were operated under local and spinal anaesthesia respectively. The patients were assessed postoperatively at 6 hrs, 8 hrs and 12 hrs on day one and then on subsequent days for different parameters like post operative pain, need and duration of analgesia required, bleeding, voiding problems and associated nausea.Result: The results of two groups were then compared and analysed. In group A 56% of patients required analgesia 8 hourly as compared to 40% in group B. No analgesics were required 3 days after the surgery in both the groups. Difficulty in voiding was seen in 12% of patients in group A as compared to 28% in group B. There was no post operative bleeding except for 4 patients in group A. Most of the patients of group A had hospital stay of 2.3±0.46 days postoperatively while those in group B stayed for 3.4±0.53 days.Conclusion: The study reveals favoured local anaesthesia over spinal anaesthesia for peri anal surgeries because of simplicity in administration of anaesthetic agent, less need of analgesia, lesser hospital stay, lesser incidence of nausea and vomiting and no need for catheterisation.